Wnt signaling in the vessel wall. Issue 3 (May 2017) - Badimon, Lina; Borrell-Pages, Maria
Abstract : Purpose of review: Wnt signaling plays a crucial role during embryogenesis. In an adult, Wnt is mainly associated to cellular proliferation and differentiation mechanisms. Recent data suggest that Wnt signaling is involved in the pathophysiology of atherosclerosis. However, the roles of Wnt signaling pathways in the vessel wall are poorly understood. This review outlines recent discoveries in understanding the role of Wnt pathways in healthy and atherosclerotic vessels. Recent findings: In the last years, the involvement of both canonical and noncanonical Wnt pathways in the development of atherosclerotic lesions has been recognized. Indeed, several Wnt pathway components have been shown to participate in the early, intermediate, and late stages of atherosclerosis development. Specifically, the role of the Wnt coreceptors low-density lipoprotein receptor-related protein 5 and low-density lipoprotein receptor-related protein 6 seems to be crucial for atherosclerotic plaque progression. Summary: Many of the clinical trials developed in the last decade to reduce atherosclerosis and cardiovascular diseases have been futile or have failed possibly because of a poor understanding of new mechanisms that lead to diseases. The understanding of the signaling pathways involved in human atherosclerosis development should help in the development of future therapies.